How do digital financial literacy, financial behavior, and skills affect financial well-being? An Exploratory Study on Gen Z - Muat, Susnaningsih; Fachrurrozi, Fachrurrozi; Sari, Nana (Integrated Journal of Business and Economics (IJBE), 2024)
Rapid development in the digital financial landscape nowadays requires individuals to have sufficient financial literacy and master digital financial literacy. This study aims to analyze the direct relationship between DFL, financial behaviour, and financial skill on FWB and investigate the mediation effect of financial behaviour and skills on the relationship between DFL and FWB. Motivated by the worrying financial condition of Generation Z, this exploratory study is conducted using a self-administered questionnaire distributed in Riau Province, which resulted in 108 valid responses. A variance-based structural equation modeling using SmartPLS is utilized to test the relationship between constructs. Findings reveal that financial behavior and financial skills directly influence FWB. The evidence showed that DFL influences FWB indirectly through financial behavior. This research suggests that the government and policymakers provide knowledge about DFL to Generation Z.